Gut Feelings: Vagal Stimulation Reduces Emotional Biases. (1st July 2022) - Johnson, Katerina V.-A.; Steenbergen, Laura
Highlights: We investigate effect of transcutaneous vagus nerve stimulation on emotional biases. Within-subject design with each participant receiving active and sham stimulation. Vagus nerve stimulation reduced bias towards sad faces in dot-probe task. Stimulation also reduced bias towards happy faces, indicating emotional blunting. Vagal signalling in healthy humans has capacity to influence emotional processing. Abstract: The vagus nerve is a key physical constituent of the gut–brain axis. Increasing attention has recently been paid to the role that the gut, and the microorganisms inhabiting it, play in emotion and cognition. Animal studies have revealed the importance of the vagus nerve in mediating communication between the gut microbiome and the central nervous system, resulting in changes in emotional behaviour. This has renewed interest in understanding the role of vagal signalling in human emotion, particularly since human studies have also shown that alterations in gut microbiome composition can affect emotion. While stimulating the vagus nerve can help treat some cases of severe depression, here we investigate whether vagal afferent signalling can influence emotional processing in healthy subjects. We use the dot-probe task to determine the effect of transcutaneous vagus nerve stimulation on attentional biases towards emotional stimuli in 42 volunteers. Participants received both active and sham treatments using a within-subject design. We show that transcutaneous vagus nerve stimulation reduces the emotional bias towards faces expressing sadness and happiness, indicating a decrease in emotional reactivity. While our novel findings reveal the effect that vagal signalling can have on emotional biases in healthy subjects, future studies should seek to develop our understanding of the ways in which the microbiome interacts with, and stimulates, the vagus nerve. Since we find a reduction in emotional bias, most notably towards sadness, this may partly account for the effective use of vagus nerve stimulation in treatment-resistant depression. While its clinical application currently involves surgical stimulation, our results support the potential benefit of transcutaneous vagus nerve stimulation as a non-invasive, intermittent adjunctive therapy for patients with depression, given its frequent association with emotional biases.